2020
DOI: 10.1038/s41598-020-77546-5
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network based prediction of postthrombolysis intracerebral hemorrhage and death

Abstract: Despite the salient benefits of the intravenous tissue plasminogen activator (tPA), symptomatic intracerebral hemorrhage (sICH) remains a frequent complication and constitutes a major concern when treating acute ischemic stroke (AIS). This study explored the use of artificial neural network (ANN)-based models to predict sICH and 3-month mortality for patients with AIS receiving tPA. We developed ANN models based on evaluation of the predictive value of pre-treatment parameters associated with sICH and mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 37 publications
2
29
0
1
Order By: Relevance
“…This study is the first to investigate the plasma EV cytokine profile in patients with PD, thus providing a novel platform to assess inflammation in these patients. Although any single cytokine fails to distinguish patients with PD from controls, evaluating them as a panel and analyzing them by using an artificial intelligence-assisted artificial neural network could effectively predict the neurological outcome after stroke [ 23 , 32 ]. Moreover, the significantly different plasma EV cytokine profiles in patients with PD with and without cognitive deficit suggest the role of inflammation in PD progression.…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first to investigate the plasma EV cytokine profile in patients with PD, thus providing a novel platform to assess inflammation in these patients. Although any single cytokine fails to distinguish patients with PD from controls, evaluating them as a panel and analyzing them by using an artificial intelligence-assisted artificial neural network could effectively predict the neurological outcome after stroke [ 23 , 32 ]. Moreover, the significantly different plasma EV cytokine profiles in patients with PD with and without cognitive deficit suggest the role of inflammation in PD progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the learning result of additional ANN models performed with the scaling input variable in our study were not better than the crude ANN model. In other DL studies relating to stroke, there was no mention of the effect of neural network scaling on DL performance [11,39]. Ahsan et al reported the effect of scaling on performance in various ML methods [40].…”
Section: Discussionmentioning
confidence: 99%
“…The variables were screened based on previously published articles and clinical experience [ 6 , 11 , 20 ]. Accordingly, 25 clinical variables were used in this study, and the data of the 216 patients were randomly divided into training (n = 168, 80%) and test (n = 48, 20%) sets using the Kennard-Stone algorithm.…”
Section: Methodsmentioning
confidence: 99%